2016
DOI: 10.1002/2016ja022613
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of the GNSS phase scintillation associated with two types of auroral blobs

Abstract: This study surveys space weather effects on GNSS (Global Navigation Satellite System) signals in the nighttime auroral and polar cap ionosphere using scintillation receivers, all‐sky imagers, and the European Incoherent Scatter Svalbard radar. We differentiate between two types of auroral blobs: blob type 1 (BT 1) which is formed when islands of high‐density F region plasma (polar cap patches) enter the nightside auroral oval, and blob type 2 (BT 2) which are generated locally in the auroral oval by intense pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 71 publications
(107 reference statements)
6
77
0
Order By: Relevance
“…At high latitudes, the scintillation effect on Global Positioning System (GPS) signals has been associated with phenomena like storm‐enhanced density, polar cap patches, and auroral precipitation (Alfonsi et al, ; De Franceschi et al, ; Jin et al, , ; Jin, Moen, et al, ; Li et al, ; Mitchell et al, ; Moen et al, ; Oksavik et al, ; Prikryl et al, , , ; Smith et al, ; Spogli et al, ; van der Meeren et al, , , ). The strongest GPS phase scintillations are associated with auroral blobs that are formed when polar cap patches enter the nightside auroral region (Jin et al, ; Jin, Moen, et al, ; van der Meeren et al, ). Similar results have been reported in the dayside cusp ionosphere, where the polar cap patches combined with the cusp auroral dynamics are associated with the strongest GPS phase scintillation (Jin et al, , ; Oksavik et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At high latitudes, the scintillation effect on Global Positioning System (GPS) signals has been associated with phenomena like storm‐enhanced density, polar cap patches, and auroral precipitation (Alfonsi et al, ; De Franceschi et al, ; Jin et al, , ; Jin, Moen, et al, ; Li et al, ; Mitchell et al, ; Moen et al, ; Oksavik et al, ; Prikryl et al, , , ; Smith et al, ; Spogli et al, ; van der Meeren et al, , , ). The strongest GPS phase scintillations are associated with auroral blobs that are formed when polar cap patches enter the nightside auroral region (Jin et al, ; Jin, Moen, et al, ; van der Meeren et al, ). Similar results have been reported in the dayside cusp ionosphere, where the polar cap patches combined with the cusp auroral dynamics are associated with the strongest GPS phase scintillation (Jin et al, , ; Oksavik et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the frequent intrusion of particles and energy from solar wind through the interplanetary magnetic field (IMF), large number of high-density structures are often generated in this region. In technological applications, the large-scale plasma irregularities often degrade the applications of Global Navigation Satellite System especially when combined with simultaneous particle precipitation (e.g., Jin et al, 2014Jin et al, , 2016Moen et al, 2013;Oksavik et al, 2015). SED is a plume of very high density plasma around the noon sector.…”
Section: Introductionmentioning
confidence: 99%
“…Still the long time duration (3-5 h) auroral emissions neither were studied nor characterized based on their boundary movement. Many researchers have attempted ionospheric scintillation associate to the dayside as well as nighside auroral emission (e.g., Jin et al, 2015Jin et al, , 2016Jin et al, , 2017Oksavik et al, 2015;Prikryl et al, 2015;van der Meeren et al, 2015) but, the ionospheric scintillation response on the GNSS signal caused at the poleward as well as equatorward edge of the auroral emission boundary is poorly understood. Feldstein and Galperin (1985), Lyons et al (2000), Zesta et al (2002); and references therein; have discussed the structure of the auroral emission in really great details.…”
Section: Introductionmentioning
confidence: 99%
“…Recent Ionospheric scintillation studies associated to the aurora in Arctic and Antarctica can be summarized as follows. Jin et al (2016) studied the scintillation associated with the different types of the auroral blobs and found that the scintillation caused due to the blobs is more severe than the polar cap patches. Ionospheric scintillation is mostly in the dayside noon in the auroral region (cusp region).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation